Mycorrhizal-induced calmodulin mediated changes in antioxidant enzymes and growth response of drought-stressed trifoliate orange - Huang, Yong-Ming; Srivastava, A. K.; Zou, Ying-Ning; Ni, Qiu-Dan; Han, Yu; Wu, Qiang-Sheng (Frontiers in Microbiology, 2014)
Trifoliate orange [Poncirus trifoliata (L) Raf.] is considered highly arbuscular mycorrhizal (AM) dependent for growth responses through a series of signal transductions in form of various physiological responses. The proposed study was carried out to evaluate the effect of an AM fungus (Funneliformis mosseae) on growth, antioxidant enzyme (catalase, CAT; superoxide dismutase, SOD) activities, leaf relative water content (RWC), calmodulin (CaM), superoxide anion (O2•−) and hydrogen peroxide (H2O2) concentrations in leaves of the plants exposed to both well-watered (WW) and drought stress (DS) conditions. A 58-day of DS significantly decreased mycorrhizal colonization by 60% than WW. Compared to non-AM seedlings, AM seedlings displayed significantly higher shoot morphological properties (plant height, stem diameter and leaf number), biomass production (shoot and root fresh weight) and leaf RWC, regardless of soil water status. AM inoculation significantly increased CaM and soluble protein concentrations and CAT activity, and significantly decreased O2•− and H2O2 concentration under both WW and DS conditions. The AM seedlings also exhibited significantly higher Cu/Zn-SOD and Mn-SOD activities than the non-AM seedlings under DS but not under WW, which are triggered by higher CaM levels in AM plants on the basis of correlation studies. Further, the negative correlation of Cu/Zn-SOD and Mn-SOD activities with O2•− and H2O2 concentration showed the DS-induced ROS scavenging ability of CaM mediated SODs under mycorrhization. Our results demonstrated that AM-inoculation elevated the synthesis of CaM in leaves and up-regulated activities of the antioxidant enzymes, thereby, repairing the possible oxidative damage to plants by lowering the ROS accumulation under DS condition.